BATAS-BATAS KONSTITUSIONAL HUKUM ISLAM DALAM HUKUM NASIONAL - muhamadun muhamadun; Murjazin Murjazin (JURNAL INDO-ISLAMIKA, 2018)
Indonesia is known as a country with a mixed legal system. The legal system currently in effect is dominated by three major legal systems, namely the Western legal system, the customary law system and the Islamic legal system. The basic rules that serve as guidelines and guidelines for citizens are extracted from the value system. This value system is expressed in the form of